Involving People With Lived Experience in Electronic Health Record Database Studies Reflections and Learning From the CHOOSE Study - Emma Cockcroft; Vidhi Bassi; Pearl L. H. Mok; Alex Adams; Anabel A. Claro; Alex M. Trafford; Matthew J. Carr; Darren M. Ashcroft; Emma Garavini; Rachel Temple; Roger T. Webb; Shruti Garg; et al. (Health Expectations)
ABSTRACT Background Patient and public involvement and engagement (PPIE) is integral to health research. Reporting of PPIE methods and impact is becoming increasingly common in health research. However, reporting on PPIE in studies using large, routinely collected electronic health record data sets is less common. Anecdotal evidence suggests that involvement in this research context is more challenging and offers fewer opportunities for meaningful influence on the research process. Objectives This paper reports the involvement approach for a Clinical Practice Research Datalink (CPRD) study and critically reflects on the process and impact of involving young people, parents and carers in research using this UK primary care electronic health record data set. Methods The CHOOSE study investigated mental health diagnoses of children and young people (1–24 years) during the COVID‐19 pandemic using the CPRD. The study was informed by a Lived Experience Advisory Panel (LEAP) which consisted of 13 members including 8 young people (13–25 years) with lived experience of mental health difficulties and 5 parents/carers, with involvement activities facilitated by project partners, mental health research charity, The McPinR Foundation. We reflect on this process in this manuscript. Results Key benefits of involving people with lived experience in this research included making sense of and contextualising findings and ensuring that they were focused on making a difference to young people's lives. Challenges included the fixed nature of the CPRD data, which did not capture all the information people with lived experience perceived to be important. Researchers expressed limited time for PPIE activities although that was compensated by McPin colleagues who organised and facilitated online meetings, and supported the young people, parents and carers during and between meetings. Conclusions This paper describes an approach to patient and public involvement in an electronic health record database study. Working collaboratively with young people, carers and other stakeholders requires sufficient time and adequate resources. We also highlight the importance of appropriate training and support and being transparent about the limitations of PPIE involvement. Patient or Public Contribution Three members of the CHOOSE LEAP have been involved in conceptualising and writing this paper.